Analisis Strategi Pemasaran I Phone Inter dan I Phone Resmi di Kota Surabaya - Giati Rahayu; Sri Prilmayanti Awaluddin (Master Manajemen, 2024)
The research aims to understand market dynamics, identify advantages and disadvantages of official iPhone Inter and iPhone, and formulate effective marketing strategies to increase official iPhone sales in Indonesia. The study uses qualitative methods with in-depth interviews and targeted group discussions to gain insight into perceptions, preferences, and factors that influence consumer purchasing decisions. Research results show that the smartphone market in Indonesia is heavily influenced by price sensitivity and consumer awareness of warranty and after-sales service. The iPhone Inter attracts consumers because of its cheaper price, although without official warranties and reliable after-sales service, while the official iPhone is more in demand by consumers who value quality assurance and trusted technical support. The study found a gap in consumer understanding of the risks and benefits of each category of iPhones. Therefore, marketing strategies for official iPhones should focus on consumer education about the risks of buying an iPhone Inter and the benefits of purchasing an official iPhone. Marketing campaigns that emphasize quality, authenticity, and after-sales support, as well as increased accessibility and financing variations for official iPhones, are expected to change consumer perceptions and encourage them to choose official products. With the right approach, Apple and its distributors can strengthen the official iPhone position in the Indonesian market, reduce the iPhone Inter market share, and win competition in this competitive market. Based on these findings, the study recommends marketing strategies that focus on consumer education about the risks of purchasing an iPhone Inter and the benefits of buying an official iPhone, as well as improved after-sales services to strengthen the official iPhone position in the Indonesian market.